Bazooka is a permissive factor for the invasive behavior of discs large tumor cells in Drosophila ovarian follicular epithelia. - Abdelilah-Seyfried, S.; Cox, D.N.; Jan, Y.N. (Development, 2003)
Drosophila Bazooka and atypical protein kinase C are essential for epithelial polarity and adhesion. We show here that wild-type bazooka function is required during cell invasion of epithelial follicle cells mutant for the tumor suppressor discs large. Clonal studies indicate that follicle cell Bazooka acts as a permissive factor during cell invasion, possibly by stabilizing adhesion between the invading somatic cells and their substratum, the germline cells. Genetic epistasis experiments demonstrate that bazooka acts downstream of discs large in tumor cell invasion. In contrast, during the migration of border cells, Bazooka function is dispensable for cell invasion and motility, but rather is required cell-autonomously in mediating cell adhesion within the migrating border cell cluster. Taken together, these studies reveal Bazooka functions distinctly in different types of invasive behaviors of epithelial follicle cells, potentially by regulating adhesion between follicle cells or between follicle cells and their germline substratum.